A Genome‐Wide Association Study of Autism Incorporating Autism Diagnostic Interview–Revised, Autism Diagnostic Observation Schedule, and Social Responsiveness Scale. Issue 1 (30th August 2012) - Connolly, John J.; Glessner, Joseph T.; Hakonarson, Hakon
<x xml:space="preserve">Abstract</x> Efforts to understand the causes of autism spectrum disorders (ASDs) have been hampered by genetic complexity and heterogeneity among individuals. One strategy for reducing complexity is to target endophenotypes, simpler biologically based measures that may involve fewer genes and constitute a more homogenous sample. A genome‐wide association study of 2, 165 participants (mean age = 8.95 years) examined associations between genomic loci and individual assessment items from the Autism Diagnostic Interview–Revised, Autism Diagnostic Observation Schedule, and Social Responsiveness Scale. Significant associations with a number of loci were identified, including KCND2 (overly serious facial expressions), NOS2A (loss of motor skills), and NELL1 (faints, fits, or blackouts). These findings may help prioritize directions for future genomic efforts.